2021
DOI: 10.24452/sjer.43.3.9
|View full text |Cite
|
Sign up to set email alerts
|

“So I had to give it up”: The role of social support for career persistence or attrition in a qualitative sample of second career teachers

Abstract: This qualitative study uses the Job Demands-Resources framework to examine social support and its role in career retention or attrition among Swiss second career teachers (SCTs). In many countries, including Switzerland, great efforts are made to bring professionals from other occupational fields into teaching. As a result, the number of SCTs is growing, as are speculations about their skills, resources, and career persistence. A qualitative content analysis of 23 semi-structured interviews shows that support … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Finally, there is an opportunity to contribute empirical evidence of the growing SCT phenomenon in Switzerland. This, then, responds to the identified need to further research the SCT phenomenon in this location (Bauer & Troesch, 2019;Bauer et al, 2021; and the recent call for more perspectives in career research (Sullivan & Al Ariss, 2019). In summary, this research is an opportunity to conceptualise the SCT phenomenon as a transformational experience that is informed by an interdisciplinary, constructive perspective.…”
Section: Research Opportunitiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, there is an opportunity to contribute empirical evidence of the growing SCT phenomenon in Switzerland. This, then, responds to the identified need to further research the SCT phenomenon in this location (Bauer & Troesch, 2019;Bauer et al, 2021; and the recent call for more perspectives in career research (Sullivan & Al Ariss, 2019). In summary, this research is an opportunity to conceptualise the SCT phenomenon as a transformational experience that is informed by an interdisciplinary, constructive perspective.…”
Section: Research Opportunitiesmentioning
confidence: 91%
“…Similarly, previous research has emphasised the value of support from experienced colleagues for new teachers (Anderson et al, 2014;Bauer et al, 2021;Fry & Anderson, 2011;Gordon, 2019;Haim & Amdur, 2016;Ilmer et al, 2005;O'Connor et al, 2011). In addition, previous research demonstrated a tendency to prioritise negative emotions and experiences, such as rejecting mentors due to age differences and problematic aspects of support relationships such as professional disagreements and expectations to accept role-modelling (Gordon, 2019;Haim & Amdur, 2016;Ilmer et al, 2005;Morton et al, 2006).…”
Section: Accentuating Social Professional Supportmentioning
confidence: 97%
See 1 more Smart Citation